Una encrucijada educativa. Tecnologías de la información, alfabetización mediática y desigualdad social - Amar, Mariano (2014)
This article proposes to deploy some considerations concerning the strong links between changes in the field of information technology and communication (ITCs) and the difficulties of the school system to a series of transformations to mobilize curriculum. In this sense, it addresses the conflict between teachers trained in a school culture bookish and scholarly pretensions and students socialized, among other agencies, by peer market/mass media. Also problematizes School contributions to the reproduction of social inequalities in access and use of ITCs, and some possible political-educational interventions to reverse this process.